Research Thinking for Responsive Teaching: Research Skill Development with In-service and Preservice Educators - I Gede Budi Mahendra; Benyamin Limbong Tampang (University of Windsor, 2024)
The book focuses on responsive teaching, highlighting the importance of adaptability and the effective utilization of resources to meet the needs of diverse learners. In the context of Education 4.0, digital literacy is crucial; however, educators also require clear objectives and a comprehensive understanding of their practices to maintain professional autonomy. The book presents the Research Skills Development (RSD) framework to guide teachers' research thinking across various contexts, including secondary schools in Australia and Canada, as well as pre-service teacher education in Indonesia and the United States.